Makna Dan Asal Usul Tasawuf Takhalli Tahalli, Dan Tajalli Serta Hubungannya Dengan Maqamat Dan Ahwal - Ferlita Anggreni; Rahmi Damis; Afifuddin Haritsah (4, 2026)
This study aims to comprehensively examine the meaning and origins of Sufism, the concepts of takhalli, tahalli, tajalli, and their relationship to the maqamat and ahwal. Using a qualitative approach with a library method that examines classical and contemporary books, this study found that Sufism is an esoteric dimension of Islam that fundamentally emphasizes the purification of the soul through tazkiyat al-nafs. The concept of takhalli is interpreted as a process of emptying oneself from all despicable traits such as arrogance, riya, and hasad. Tahalli is the stage of adorning oneself with praiseworthy morals such as patience, gratitude, and tawakkul. Meanwhile, tajalli is the revelation of Divine light which is a gift for a purified soul. These three stages form a systematic and sequential spiritual process, where takhalli is a prerequisite for tahalli, and both pave the way for tajalli. Furthermore, these three stages are closely correlated with maqamat, which are spiritual stations that can be achieved through sincere effort and struggle, and ahwal, which are inner states that come as gifts and blessings from Allah alone. The relationship between the two is dynamic, because a solid maqamat will give birth to stable ahwal, while ahwal can strengthen the achievement of higher maqamat. An integrative understanding of these six concepts is crucial for those who travel the spiritual path, because it provides a complete picture of the spiritual journey map in Islam, from the effort of self-purification to the attainment of ma'rifatullah. This research contributes to formulating a theoretical framework that connects the practical and theological aspects of Islamic spirituality, while also offering guidance for modern Sufism practitioners in actualizing these values ​​in the midst of contemporary life. Abstrak Penelitian ini bertujuan mengkaji secara komprehensif makna dan asal usul tasawuf, konsep takhalli, tahalli, tajalli, serta hubungan ketiganya dengan maqamat dan ahwal. Menggunakan pendekatan kualitatif dengan metode kepustakaan yang menelaah kitab-kitab klasik dan kontemporer, penelitian ini menemukan bahwa tasawuf merupakan dimensi esoterik Islam yang secara fundamental menekankan penyucian jiwa melalui tazkiyat al-nafs. Konsep takhalli dimaknai sebagai proses pengosongan diri dari segala sifat tercela seperti takabur, riya, dan hasad. Tahalli merupakan tahap penghiasan diri dengan akhlak terpuji seperti sabar, syukur, dan tawakal. Sementara itu, tajalli adalah penyingkapan cahaya Ilahi yang merupakan anugerah bagi jiwa yang telah suci. Ketiga tahap ini membentuk proses spiritual yang sistematis dan berurutan, di mana takhalli menjadi prasyarat bagi tahalli, dan keduanya membuka jalan bagi tajalli. Lebih lanjut, ketiga tahapan tersebut berkorelasi erat dengan maqamat yang merupakan stasiun-stasiun spiritual yang dapat dicapai melalui usaha dan perjuangan sungguh-sungguh, serta ahwal yang merupakan keadaan batiniah yang datang sebagai pemberian dan karunia dari Allah semata. Hubungan antara keduanya bersifat dinamis, karena maqamat yang kokoh akan melahirkan ahwal yang stabil, sementara ahwal dapat memperkuat pencapaian maqamat yang lebih tinggi. Pemahaman integratif terhadap keenam konsep ini sangat penting bagi para penempuh jalan spiritual, karena memberikan gambaran utuh tentang peta perjalanan ruhani dalam Islam, mulai dari upaya pembersihan diri hingga pencapaian ma'rifatullah. Penelitian ini berkontribusi dalam merumuskan kerangka teoretis yang menghubungkan aspek praktis dan teologis dalam spiritualitas Islam, sekaligus menawarkan panduan bagi praktisi tasawuf modern dalam mengaktualisasikan nilai-nilai tersebut di tengah kehidupan kontemporer